Proto-oncogene HER-2 in normal, dysplastic and tumorous feline mammary glands: an immunohistochemical and chromogenic in situ hybridization study - Ordás, Javier (BioMed Central, 2007)
BACKGROUND: Feline mammary carcinoma has been proposed as a natural model of highly aggressive, hormone-independent human breast cancer. To further explore the utility of the model by adding new similarities between the two diseases, we have analyzed the oncogene HER-2 status at both the protein and the gene levels. METHODS: Formalin-fixed, paraffin-embedded tissue samples from 30 invasive carcinomas, 7 benign lesions and two normal mammary glands were analyzed. Tumour features with prognostic value were recorded. The expression of protein HER-2 was analyzed by immunohistochemistry and the number of gene copies by means of DNA chromogenic in situ hybridization. RESULTS: Immunohistochemical HER-2 protein overexpression was found in 40% of feline mammary carcinomas, a percentage higher to that observed in human breast carcinoma. As in women, feline tumours with HER-2 protein overexpression had pathological features of high malignancy. However, amplification of HER-2 was detected in 16% of carcinomas with protein overexpression, a percentage much lower than that observed in their human counterpart. CONCLUSION: Feline mammary carcinoma would be a suitable natural model of that subset of human breast carcinomas with HER-2 protein overexpression without gene amplification.